2022
DOI: 10.1017/erm.2022.28
|View full text |Cite
|
Sign up to set email alerts
|

Roles of CCR10/CCL27–CCL28 axis in tumour development: mechanisms, diagnostic and therapeutic approaches, and perspectives

Abstract: Cancer is now one of the major causes of death across the globe. The imbalance of cytokine and chemokine secretion has been reported to be involved in cancer development. Meanwhile, CC chemokines have received considerable interest in cancer research. CCR10, as the latest identified CC chemokine receptor (CCR), has been implicated in the recruitment and infiltration of immune cells, especially lymphocytes, into epithelia such as skin via ligation to two ligands, CCL27 and CCL28. Other than homoeostatic functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
(146 reference statements)
0
2
0
Order By: Relevance
“… 29 CCR10/CTACK interaction may relate to the development of sarcopenia due to their crucial roles in regulating multiple immune cells with conflicting effects, including helper T cells, cytotoxic T cells, regulatory T cells, natural killer cells, myeloid‐derived suppressor cells and so on. 30 However, few studies have reported the relationships between CTACK and sarcopenia. More research is needed to elucidate the relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 CCR10/CTACK interaction may relate to the development of sarcopenia due to their crucial roles in regulating multiple immune cells with conflicting effects, including helper T cells, cytotoxic T cells, regulatory T cells, natural killer cells, myeloid‐derived suppressor cells and so on. 30 However, few studies have reported the relationships between CTACK and sarcopenia. More research is needed to elucidate the relationships.…”
Section: Discussionmentioning
confidence: 99%
“…CTACK–CCR10 signalling is involved in the regulation of immune responses, including the recruitment of T cells to the skin during inflammation and the formation of immunological synapses between dendritic cells and T cells 29 . CCR10/CTACK interaction may relate to the development of sarcopenia due to their crucial roles in regulating multiple immune cells with conflicting effects, including helper T cells, cytotoxic T cells, regulatory T cells, natural killer cells, myeloid‐derived suppressor cells and so on 30 . However, few studies have reported the relationships between CTACK and sarcopenia.…”
Section: Discussionmentioning
confidence: 99%